Na2YMg2(VO4)3:Er3+, Yb3+ phosphors: Up-conversion and optical thermometry. Issue 2 (15th January 2021) - Tong, Ye; Zhang, WenNa; Wei, RongFei; Chen, LiPing; Guo, Hai
Abstract: Herein, Na2 YMg2 (VO4 )3 :Er 3+, Yb 3+ phosphors are reported for up-conversion (UC) luminescent material as optical thermometry relied on fluorescence intensity ratio (FIR) and fluorescence lifetime. Their structures, UC luminescent properties and temperature sensing properties have been systematically investigated. Heavy doping of Er 3+ and Yb 3+ ions with maximal content of 59% is realized, which is beneficial to obtain highly efficient UC luminescence. Excited by 980 nm laser, Er 3+ and Er 3+, Yb 3+ doped phosphors give 525, 550 and 660 nm emissions, which are originated from 2 H11/2, 4 S3/2 and 4 F9/2  →  4 I15/2 transitions of Er 3+ ions, respectively. The reasonable UC mechanism is discussed in detail. What's more, the UC emissions of all samples dominate in green area from thermally coupled 2 H11/2 / 4 S3/2 levels of Er 3+ ions, which is helpful to obtain better temperature sensing performances. And the maximal relative sensitivities of FIR and fluorescence lifetime methods reach 1.104 %K −1 (303 K) and 0.087 %K −1 (412 K), respectively. All results manifest that Na2 YMg2 (VO4 )3 :Er 3+, Yb 3+ phosphors are good potential alternative for optical temperature sensors.